FRI0391 GLYCA, A Novel Marker of Inflammation, Is Elevated in Systemic Lupus Erythematosus. (9th June 2015) - Chung, C.P.; Ormseth, M.J.; Connelly, M.A.; Oeser, A.; Solus, J.F.; Otvos, J.; Raggi, P.; Stein, C.M.
Abstract : Background: GlycA is a novel marker of systemic inflammation detected by nuclear magnetic resonance spectroscopy (NMR). It arises from the N-acetyl methyl signals from glycosylated acute phase proteins. Several glycoproteins, including α-1 antichymotrypsin, haptoglobin, α-1-antitrypsin, transferrin, and α1-acid glycoprotein (AGP, orosomucoid) contribute significantly to increase the GlycA signal during inflammation. In the general population, GlycA is correlated with inflammatory markers such as C-reactive protein (CRP) and associated with coronary heart disease and diabetes. The utility of GlycA in patients with systemic lupus erythematosus (SLE) has not been defined. Objectives: To test the hypothesis that GlycA concentrations were elevated in patients with SLE and associated with other markers of inflammation and with coronary atherosclerosis. Methods: We compared concentrations of GlycA in 116 patients with SLE and 84 control subjects frequency-matched for age, sex, and race. GlycA was detected by NMR. SLE disease activity index (SLEDAI) and the SLE Collaborating Clinics damage index (SLICC) were calculated. Acute phase reactants [erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP)], a panel of cytokines and a lipid panel were measured. Electron beam computer tomography (EBCT) was used to quantify coronary artery calcification, a measure of coronary artery atherosclerosis. Results: Patients with SLE had higher concentrations of GlycA [398 (350-445)] than control subjects [339 (299-391)] μmol/L, p<0.001. In patients with SLE, concentrations of GlycA were significantly associated with ESR (rho=0.43), CRP (rho=0.59), interleukin-6 (rho=0.27), e-selectin (rho=0.28), intracellular adhesion molecule-1 (rho=0.30), HDL cholesterol (rho=-0.26), triglycerides (rho=0.45), systolic (rho=0.23), and diastolic blood pressure (rho=0.21), all p<0.05, but not with creatinine, SLEDAI, SLICC, or coronary calcium scores. Conclusions: Concentrations of GlycA are higher in patients with SLE than control subjects and associated with markers of inflammation but not with SLE disease activity or chronicity scores or coronary artery calcification. Disclosure of Interest: C. Chung: None declared, M. Ormseth: None declared, M. Connelly Employee of: LabCorp, A. Oeser: None declared, J. Solus: None declared, J. Otvos Employee of: LabCorp, P. Raggi: None declared, C. M. Stein: None declared